2019
DOI: 10.1093/database/bay141
|View full text |Cite
|
Sign up to set email alerts
|

EnhancerDB: a resource of transcriptional regulation in the context of enhancers

Abstract: Enhancers can act as cis-regulatory elements to control transcriptional regulation by recruiting DNA-binding transcription factors (TFs) in a tissue-specific manner. Recent studies show that enhancers regulate not only protein-coding genes but also microRNAs (miRNAs), and mutations within the TF binding sites (TFBSs) located on enhancers will cause a variety of diseases such as cancer. However, a comprehensive resource to integrate these regulation elements for revealing transcriptional regulations in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…3d and Supplementary Table 11). Interestingly, variant rs146239222 is found in an enhancer region 48, 49 with high H3K27ac modification, DNase clusters, and multiple transcription factor binding, which is also consistent with the output of the CARMEN annotation module (Supplementary Fig. 10c,d), and is associated with the expression of MPHOSPH9 in GTEx ( p = 1.34 × 10 −91 , ENSG00000051825.10) 50 .…”
Section: Resultssupporting
confidence: 74%
“…3d and Supplementary Table 11). Interestingly, variant rs146239222 is found in an enhancer region 48, 49 with high H3K27ac modification, DNase clusters, and multiple transcription factor binding, which is also consistent with the output of the CARMEN annotation module (Supplementary Fig. 10c,d), and is associated with the expression of MPHOSPH9 in GTEx ( p = 1.34 × 10 −91 , ENSG00000051825.10) 50 .…”
Section: Resultssupporting
confidence: 74%
“…( 68–72 ) Numerous potential transcription factor binding sites within the 2000‐bp H3K27ac enrichment peak in the Pth1r promoter were identified and are summarized in Supplementary Table S1. ( 73 ) One promising transcription factor, Ying Yang 1 (YY1), showed increased binding at the Pth1r promoter in response to Phlpp inhibition. YY1 is a dual function transcription factor that regulates both transcriptional activation and repression and has been implicated in a host of cellular processes, including differentiation, DNA repair, cell division, and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as a single histone mark is not a reliable CRM predictor, a great deal of efforts have been made to predict CRMs based on multiple histone marks and chromatin accessibility (CA) data from the same cell/tissue types using various machine-learning methods, including hidden Markov models(Ernst & Kellis, 2012), dynamic Bayesian networks(Hoffman et al, 2013), time-delay neural networks(Firpi, Ucar, & Tan, 2010), random forest(Rajagopal et al, 2013), and support vector machines (SVMs)(Kleftogiannis, Kalnis, & Bajic, 2015). Many enhancer databases have also been created either by combining results of multiple such methods(Ashoor, Kleftogiannis, Radovanovic, & Bajic, 2015; Fishilevich et al, 2017; Zerbino, Wilder, Johnson, Juettemann, & Flicek, 2015), or by identifying overlapping regions of CA and histone mark tracks in the same cell/tissue types(Chen et al, 2020; Cheneby, Gheorghe, Artufel, Mathelier, & Ballester, 2018; Gao & Qian, 2020; Kang et al, 2019; G. Zhang et al, 2018). In particular, most recently, the ENCODE phase 3 consortium(Moore et al, 2020) identified 926,535 candidate cis -regulatory elements (cCREs) based on overlaps between millions of DNase I hypersensitivity sites (DHSs)(Thurman et al, 2012) and transposase accessible sites (TASs)(Buenrostro, Giresi, Zaba, Chang, & Greenleaf, 2013), active promoter histone mark H3K4me3(Aday, Zhu, Lakshmanan, Wang, & Lawson, 2011) peaks, active enhancer mark H3K27ac(Creyghton et al, 2010) peaks, and insulator mark CTCT(Kim et al, 2007) peaks in a large number of cell/tissue types.…”
Section: Introductionmentioning
confidence: 99%